Physicochemical composition and antioxidants of buriti (Mauritia flexuosa Linn. F.) – pulp and sweet - Nara Rúbia Rodrigues Nascimento-Silva; Flávio Alves Silva; Mara Reis Silva (Journal of Bioenergy and Food Science, 2020)
Buriti pulp has an elevated nutritional value and commercial potential, mainly because of its significant amounts of bioactive compounds. The objective of this research was to evaluate the physicochemical characteristics, the antioxidant capacity, and bioactive compounds of buriti pulps and sweets obtained from the Brazilian states of Goiás, Tocantins and Para. The fruits obtained from Tocantins and Para presented greater lipid and energy contents. After processing, the sweets showed reductions in the protein, lipid, fiber and bioactive compound contents. The antioxidant activities and total phenolic compound contents were more significant in the pulp and sweets from Goiás. There was a strong correlation between the phenolic compounds and the antioxidant activity. The total carotenoid content was greater in the buriti pulp and sweet from Tocantins but an 80% reduction in the bioactive compounds was observed in all the sweets produced. Thus, it was concluded that the origin of the fruit influenced its chemical composition and the antioxidant activity. However fruits and sweets can still be considered good dietary sources of bioactive compounds especially carotenoids.